Distinguishing between determinate and indeterminate growth in a long-lived mammal - Mumby, Hannah S. (BMC Evol Biol, 2015)
BACKGROUND: The growth strategy of a species influences many key aspects of its life-history. Animals can either grow indeterminately (throughout life), or grow determinately, ceasing at maturity. In mammals, continued weight gain after maturity is clearly distinguishable from continued skeletal growth (indeterminate growth). Elephants represent an interesting candidate for studying growth because of their large size, long life and sexual dimorphism. Objective measures of their weight, height and age, however, are rare. RESULTS: We investigate evidence for indeterminate growth in the Asian elephant Elephas maximus using a longitudinal dataset from a semi-captive population. We fit growth curves to weight and height measurements, assess sex differences in growth, and test for indeterminate growth by comparing the asymptotes for height and weight curves. Our results show no evidence for indeterminate growth in the Asian elephant; neither sex increases in height throughout life, with the majority of height growth completed by the age of 15 years in females and 21 years in males. Females show a similar pattern with weight, whereas males continue to gain weight until over age 50. Neither sex shows any declines in weight with age. CONCLUSIONS: These results have implications for understanding mammalian life-history, which could include sex-specific differences in trade-offs between size and reproductive investment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0487-x) contains supplementary material, which is available to authorized users.